(untitled) (KULT_online, 2023)
In her dissertation Carina Rech analyzes Nordic women painter’s professional Self-fashioning in the 1880s. The women artists under consideration lived in Paris during the 1880s for different periods of time, which was fundamental for their professional development. By means of selected works of these women artists as well as written sources – amongst other things correspondences, reviews and newspaper articles – Carina Rech studies this topic. Thereby, the focus is on emulation, collaboration and appropriation as strategies.